Dyeing Jumput Batik Using Clay Media From the Malo Region, Bojonegoro - Henny Indah Pratiwi; Fianti Fianti; Ian Yulianti (Universitas Negeri Semarang, 2023)
Indonesian clay, with red color type was one kind of clay with wide distribution and yet to be well managed. The clay can be used as natural coloring material as a substitute for the textile dyes. This study aims to determine the effect of soaking time on the color produced and the effect of clay solution composition on the color produced. The variable used in this research is the variation of the solution composition (1kg/ 1 L, 1kg/ 2L, 1kg/ 3L) and variation of soaking time (24 hours, 48 hours, and 72 hours). The results of the research show that on the solution composition variation obtained the most concentrated color at 1kg/ 1L solution, and at the soaking time variation obtained the most concentrated color at 72 hours with the intensity of light that can penetrate the fabric is very small.